PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM ALOKASI DANA - Oni Nugrianti; Zulkarnaini ' (Universitas Riau, 2013)
Through Community Empowerment Program Allocation. The purpose of thisstudy is to investigate and analyze the factors that influence the empowerment of rural communitiesthrough village fund allocation (ADD) in District Central Kuantan Kuantan District Singingi. Thisresearch was conducted in the Central District of Kuantan Kuantan District Singingi, where theinformant is research officer involved in the ADD program, community leaders and prominentscholars who know the ADD program. Data collected by interview and observation techniques,after the data was collected and then analyzed using qualitative descriptive analysis. The resultsshow the effectiveness of community empowerment through ADD program in District CentralKuantan Kuantan District Singingi still not running smoothly or less effective, while the dominantfactor influencing factor is fear.